1985
DOI: 10.1111/j.1834-7819.1985.tb02528.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatized anterior teeth amongst high school students in northern Sydney

Abstract: Abstract— The prevalence and severity of fractures of anterior teeth among 12 287 high school students in two areas of northern Sydney was recorded. Overall, six per cent of students had suffered fractures involving dentine or pulp. Twenty‐three per cent of these teeth were non vital. In the less affluent area more fractured teeth remained untreated. Trauma prevalence was twice as high amongst boys as girls; body contact, sports, and bicycles contributed most to this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 0 publications
5
40
0
Order By: Relevance
“…2,3 More recent investigations through clinical examinations of large adolescent populations and surveys of lay knowledge on the management of avulsed teeth provide dentoalveolar trauma incident estimates ranging from 6-34%. 1, [3][4][5][6] These reports confirm that dentists are confronted with managing dental trauma and restoring fractured teeth on a regular basis. Techniques that speed and simplify treatment, restore aesthetics, and improve long-term success rates are therefore of potential value and should be considered.…”
Section: Practicementioning
confidence: 62%
“…2,3 More recent investigations through clinical examinations of large adolescent populations and surveys of lay knowledge on the management of avulsed teeth provide dentoalveolar trauma incident estimates ranging from 6-34%. 1, [3][4][5][6] These reports confirm that dentists are confronted with managing dental trauma and restoring fractured teeth on a regular basis. Techniques that speed and simplify treatment, restore aesthetics, and improve long-term success rates are therefore of potential value and should be considered.…”
Section: Practicementioning
confidence: 62%
“…[1][2][3][4] These sub-populations represent a small portion of the general Australian population. Davis and Knott 5 in 1984 studied patients presenting with dental trauma to members of the Australian Society of Endodontology, Australia-wide.…”
Section: Introductionmentioning
confidence: 99%
“…However, only injuries to anterior permanent teeth were recorded. 1 Another Australian study by Burton et al 2 found a prevalence rate of 6 per cent of dental trauma in 12 287 secondary school students. A contrasting study in England, by Hamilton 8 established a 34 per cent prevalence rate of dental trauma in 2022 secondary school students.…”
mentioning
confidence: 99%
“…prevalence ranges from 6 3 to 34 per cent. 6 Stockwell's study of injury to the permanent dentition in the Western Australian School Dental Service established an incidence rate of 1.7 per cent per year in 6-12 year olds.…”
mentioning
confidence: 99%
“…15 Previous investigations into paediatric dental trauma have sought to clarify the incidence, demographic details of patients suffering injuries, aetiology, injury subtypes and treatment. [1][2][3][4][5][6][7][8][9][10][11][12][14][15][16][17][18] Little information is available on the causes of delays in the treatment of children who present with dento-alveolar trauma. The specific objectives of this study were to profile the time course from injury to treatment and quantify treatment…”
mentioning
confidence: 99%